Update on Rivaroxaban - Osama Moussa; Dipankar Chattopadhyay; Vish Bhattacharya (Clinical Medicine Insights: Blood Disorders, 2010)
Anticoagulants are recommended for the prevention and treatment of venous thromboembolism (VTE). The new anticoagulants which target specific factors in the coagulation cascade offer the advantage that they can be administered orally. These drugs seek to offer safe anticoagulation without the need for regular monitoring and frequent dose adjustment. Some of these newer drugs are in the advanced stages of clinical trials or have already completed them and thereby aim to provide more options in the management of thromboembolism. In the present review we discuss the currently available evidence supporting the use of these new anticoagulants, in particular rivaroxaban.